Customer Satisfaction in the Cosmetics Retail Industry: The Roles of Service Quality and Price Perception: JEL Classification: M31; D12; D40; L66; L81 - Yopelina Dowansiba; Roberth Kurniawan Ruslak Hammar; Lucia K Rahaded (Newinera Publisher, 2026)
This study aims to examine the effects of Service Quality and Price Perception on Customer Satisfaction among customers of Rain Cosmetics Manokwari. The research employed a quantitative approach involving 79 customers selected through purposive sampling. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using multiple linear regression with the assistance of Statistical Package for the Social Sciences software. Prior to hypothesis testing, the research instrument was evaluated through validity and reliability tests, while the regression model was assessed using classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The findings indicate that all measurement items are valid and reliable, and the regression model satisfies the required statistical assumptions. The results reveal that Service Quality has a positive and significant effect on Customer Satisfaction. Price Perception also exerts a positive and significant effect on Customer Satisfaction and emerges as the most influential variable affecting customer satisfaction. Simultaneously, Service Quality and Price Perception significantly influence Customer Satisfaction and explain a substantial proportion of customer satisfaction variations. The findings suggest that customer satisfaction in the cosmetics retail industry is influenced by both positive service experiences and favorable perceptions regarding price fairness and value. The study concludes that improving service performance and maintaining appropriate pricing strategies are essential for enhancing customer satisfaction and strengthening competitiveness in the cosmetics retail sector